2020
DOI: 10.1088/2053-1591/abd068
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of LZ91 magnesium alloy processed by asynchronous accumulative roll bonding

Abstract: In order to expand the application prospects of LZ91 magnesium alloy, improve its tensile strength and yield strength. In this paper, the asynchronous rolling and cumulative rolling technology are combined in the large plastic deformation technology, and the LZ91 magnesium alloy after coating the aluminum foil by the asynchronous accumulative roll bonding is performed. The analysis shows that the asynchronous accumulative roll bonding technology accumulates a large amount of deformation energy storage inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, the addition of Zn hardens both the  and  phases, and work hardening behavior is enhanced by both Zn addition and an increase of the  phase. A separate study, also reported an increase in strength and a decrease in elongation with rolling passes owing to grain refinement and dislocation tangles for Mg-9Li-1Zn alloy [38]. An investigation on the mechanism of phase refinement of extruded Mg-7.8Li-0.8Zn alloy revealed that severely deformed  phase can be refined by post rolling annealing [39].…”
Section: Design Considerations For Mg-li Based Alloysmentioning
confidence: 94%
“…Furthermore, the addition of Zn hardens both the  and  phases, and work hardening behavior is enhanced by both Zn addition and an increase of the  phase. A separate study, also reported an increase in strength and a decrease in elongation with rolling passes owing to grain refinement and dislocation tangles for Mg-9Li-1Zn alloy [38]. An investigation on the mechanism of phase refinement of extruded Mg-7.8Li-0.8Zn alloy revealed that severely deformed  phase can be refined by post rolling annealing [39].…”
Section: Design Considerations For Mg-li Based Alloysmentioning
confidence: 94%
“…6,7 With the addition of Li, the c/a ratio decreases from 1.624 (pure Mg) to 1.607 (Mg-17 at.% Li), from which the non-basal slips are operable. [8][9][10][11][12][13][14] Previous work has shown that prismatic slip was prevailing in Mg-Li alloy with increasing lithium contents. 9 When the Li content in Mg ranges from 17 to 30 at.%, the body-centred cubic (BCC) b-lithium phase appears, which improves the formability of Mg alloys dramatically at ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%